A kind of thermos cup coating and preparation method thereof
By using aqueous amino resin, polyester resin and aqueous acrylic resin cross-linking network structure, and adding nano-inorganic filler and adhesion promoter of polyurethane and tanninic acid compound, the high VOC and poor adhesion performance of traditional oil-based paints are solved. Problem, water-based coatings with high adhesion and heat resistance are achieved, meeting food-grade requirements.
Patent Information
- Application Number
- CN202310872705.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-07-17
AI Technical Summary
When traditional oil-based paint is used for thermos spraying, it has high VOC, high odor, high toxicity, and poor heat-resistant and adhesion of the paint film, which cannot meet the food grade requirements.
Use aqueous amino resin, polyester resin and aqueous acrylic resin as the main components to generate a cross-linking network structure through cross-linking of active groups, and add nano-inorganic fillers and adhesion promoters of polyurethane and tanninic acid composite to enhance the coating adhesion performance.
It significantly improves the adhesion between the coating and the thermos cup base layer, enhances the mechanical properties and heat-water resistance of the paint film, meets the food-grade requirements, and reduces VOC emissions.
Smart Images

Figure BDA0004341608980000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coatings, and more specifically, to a coating for a thermos cup and a preparation method thereof. Background Art
[0002] In the eyes of many people, only the anti-corrosion, marking, color decoration, etc. of industrial products such as automobiles and electromechanical equipment can be included in the scope of coating technology. In fact, this is a misunderstanding. There are many daily necessities and household products around us that need to be paid attention to. Among them, the surface treatment, coating effect and quality of thermos cups, as people's daily drinking tools, are related to the appearance and performance of the product, affecting the reputation and cost performance of the product and even the image of the company.
[0003] As people's living standards improve, the demand for thermos cups is increasing, and the requirements for appearance and quality are getting higher and higher. Many companies produce thermos cups in many colors, up to hundreds of colors, which are gorgeous and give customers a variety of choices. Traditional oil-based paint is used for spraying the appearance of thermos cups. It has high VOC, strong odor, and high toxicity. The paint film has poor hot water resistance and adhesion, and the paint film does not meet food grade requirements.
[0004] In recent years, people have paid more and more attention to the social environment, and local governments have become more and more strict on VOC emissions in the coating industry. Companies engaged in the coating industry have turned their attention to the water-based coating market. Although water-based coatings have greatly reduced VOC emissions, they have not solved the problem of poor adhesion between the coating and the base of the thermos cup. Therefore, it is urgent to develop a water-based coating with better adhesion to meet the use needs of the thermos cup. Summary of the invention
[0005] In order to solve the problem of poor adhesion between the coating and the thermos cup, the present application provides a thermos cup coating and a preparation method thereof.
[0006] In the first aspect, the present application provides a thermos cup coating, which adopts the following technical solution:
[0007] A coating for a thermos cup is composed of the following raw materials in parts by weight: 20-50 parts of a polyester resin, 10-25 parts of a water-based amino resin, 15-30 parts of a water-based acrylic resin, 2-5 parts of a nano inorganic filler, 5-15 parts of an adhesion promoter, and 15-25 parts of water; the adhesion promoter is prepared by compounding polyurethane and tannic acid in a mass ratio of (5-12):1.
[0008] By adopting the above technical solution, water-based amino resin, polyester resin and water-based acrylic resin are used as the main components of the thermos cup coating, and are cross-linked with each other through active groups to generate a cross-linked network structure. Nano inorganic fillers are filled in the pores of the network structure, which further improves the density of the network structure, thereby improving the mechanical properties of the coating. In addition, there is an interaction between a part of the active groups that have not participated in the cross-linking and the active groups on the surface of the thermos cup base layer, thereby improving the adhesion performance between the coating and the thermos cup base layer;
[0009] Polyurethane and tannic acid are compounded into an adhesion promoter according to the above mass ratio, which has the following effects: on the one hand, both polyurethane and tannic acid molecules contain active groups, and these active groups interact with the active groups on the base layer of the thermos cup; on the other hand, tannic acid, as a chelating agent, can complex with the metal ions on the base layer of the thermos cup, and the interaction between the active groups and the complexation jointly improve the adhesion performance between the coating and the base layer of the thermos cup;
[0010] In summary, the various substances in the raw materials of the thermos cup coating of the present application support each other functionally, and jointly improve the adhesion performance between the coating and the base layer of the thermos cup.
[0011] Preferably, the weight portion of the water-based amino resin is 20-25 parts.
[0012] Preferably, the weight portion of the water-based acrylic resin is 20-30 parts.
[0013] Preferably, the mass ratio of the polyurethane to tannic acid is (8-12):1.
[0014] Preferably, the nano inorganic filler is one or more of fumed silica, hydroxylated carbon nanotubes, and graphene oxide.
[0015] Preferably, the nano inorganic filler is fumed silica and / or hydroxylated carbon nanotubes.
[0016] By adopting the above technical solution, fumed silica and hydroxylated carbon nanotubes synergistically enhance the mechanical properties of the coating and the adhesion performance between the coating and the thermos cup.
[0017] Preferably, the thermos cup coating further comprises 1-3 parts of hydrofluoric acid.
[0018] By adopting the above technical solution, a small amount of hydrofluoric acid is added to the coating. The hydrofluoric acid can micro-etch the surface of the base layer of the thermos cup, forming multiple tiny etching points on the surface of the base layer, thereby improving the roughness of the surface of the base layer. Nano-inorganic fillers can fill the etching points and serve as mechanical anchor points between the coating and the base layer, thereby further improving the adhesion performance between the coating and the base layer.
[0019] Preferably, the weight portion of the hydrofluoric acid is 1-2 parts.
[0020] In the second aspect, the present application provides a method for preparing a thermos cup coating, using the following technical solution:
[0021] A method for preparing a vacuum flask coating comprises the following steps:
[0022] The polyester resin, water-based amino resin, water-based acrylic resin, nano inorganic filler, adhesion promoter and water are mixed and stirred to obtain the thermos cup coating.
[0023] In summary, this application has the following beneficial effects:
[0024] 1. The present application uses water-based amino resin, polyester resin, and water-based acrylic resin as the main components of the thermos cup coating, which are cross-linked through active groups to generate a cross-linked network structure. Nano inorganic fillers are filled in the pores of the network structure, further improving the density of the network structure, thereby improving the mechanical properties of the coating. In addition, there is an interaction between a part of the active groups that have not participated in the cross-linking and the active groups on the surface of the thermos cup base layer, thereby improving the adhesion performance between the coating and the thermos cup base layer;
[0025] Polyurethane and tannic acid are compounded into an adhesion promoter in the above-mentioned mass ratio, which has the following effects: on the one hand, both polyurethane and tannic acid molecules contain active groups, and there is interaction between these active groups and the active groups on the base layer of the thermos cup; on the other hand, tannic acid, as a chelating agent, can complex with the metal ions on the base layer of the thermos cup, and the interaction between the active groups and the complexation together improve the adhesion performance between the coating and the base layer of the thermos cup.
[0026] 2. In the present application, it is preferred to add a small amount of hydrofluoric acid to the coating. The hydrofluoric acid can micro-etch the surface of the base layer of the thermos cup, forming multiple tiny etching points on the surface of the base layer, thereby increasing the roughness of the surface of the base layer. Nano-inorganic fillers can fill the etching points and serve as mechanical anchor points between the coating and the base layer, thereby further improving the adhesion performance between the coating and the base layer. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to embodiments.
[0028] Unless otherwise specified, the specifications of the raw materials used in the following examples and comparative examples are shown in Table 1.
[0029] Table 1. Raw material specifications
[0030] raw material Specification Polyester resin Model:Albester3310 Waterborne amino resin Brand: 5280-60 Fumed Silica Model: A380 Hydroxylated carbon nanotubes Model: DZ-210 Water-based acrylic resin Brand: HF-05A Polyurethane Model: HB35
[0031] Preparation Example of Adhesion Promoter
[0032] Preparation Example 1
[0033] The adhesion promoter is prepared according to the following steps:
[0034] Polyurethane and tannic acid were mixed in a mass ratio of 5:1 (the total mass of polyurethane and tannic acid was 1 kg) to obtain an adhesion promoter.
[0035] Preparation Example 2
[0036] The adhesion promoter is prepared according to the following steps:
[0037] Polyurethane and tannic acid were mixed in a mass ratio of 12:1 (the total mass of polyurethane and tannic acid was 1 kg) to obtain an adhesion promoter.
[0038] Preparation Example 3
[0039] The adhesion promoter is prepared according to the following steps:
[0040] Polyurethane and tannic acid were mixed in a mass ratio of 8:1 (the total mass of polyurethane and tannic acid was 1 kg) to obtain an adhesion promoter.
[0041] Example
[0042] Example 1
[0043] A thermos cup coating, the formula of which is as follows:
[0044] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano inorganic filler, 0.5kg of adhesion promoter prepared in Preparation Example 1, 1.5kg of water, 0.1kg of pH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, and 0.075kg of wetting agent.
[0045] A thermos cup coating is prepared according to the following steps:
[0046] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0047] Step 2: Add nano inorganic filler fumed silica while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0048] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes, add adhesion promoter and stir for 5 minutes; then add wetting agent and stir for 5 minutes, add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0049] Example 2
[0050] A thermos cup coating, the formula of which is as follows:
[0051] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano inorganic filler, 0.5kg of adhesion promoter prepared in Preparation Example 2, 1.5kg of water, 0.1kg of pH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, and 0.075kg of wetting agent.
[0052] A thermos cup coating is prepared according to the following steps:
[0053] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0054] Step 2: Add nano inorganic filler fumed silica while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0055] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes, add adhesion promoter and stir for 5 minutes; then add wetting agent and stir for 5 minutes, add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0056] Example 3
[0057] A thermos cup coating, the formula of which is as follows:
[0058] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano-inorganic filler, 0.5kg of adhesion promoter prepared in Preparation Example 3, 1.5kg of water, 0.1kg of pH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, and 0.075kg of wetting agent.
[0059] A thermos cup coating is prepared according to the following steps:
[0060] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0061] Step 2: Add nano inorganic filler fumed silica while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0062] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes, add adhesion promoter and stir for 5 minutes; then add wetting agent and stir for 5 minutes, add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0063] Example 4
[0064] A thermos cup coating, the formula of which is as follows:
[0065] 5kg of polyester resin, 2.5kg of water-based amino resin, 3kg of water-based acrylic resin, 0.5kg of nano inorganic filler, 1.5kg of adhesion promoter prepared in Preparation Example 1, 2.5kg of water, 0.2kg of pH regulator, 0.4kg of dipropylene glycol butyl ether, 0.05kg of water-based dispersant, and 0.2kg of wetting agent.
[0066] A thermos cup coating is prepared according to the following steps:
[0067] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0068] Step 2: Add nano inorganic filler fumed silica while stirring, add 1kg of water to clean the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0069] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes. Add adhesion promoter and stir for 5 minutes. Then add wetting agent and stir for 5 minutes. Then add 1.5 kg water and stir for 5 minutes to obtain the thermos cup coating.
[0070] Example 5
[0071] 4kg of polyester resin, 2kg of water-based amino resin, 2kg of water-based acrylic resin, 0.4kg of nano inorganic filler, 1kg of adhesion promoter prepared in Preparation Example 1, 2kg of water, 0.15kg of pH regulator, 0.15kg of dipropylene glycol butyl ether, 0.04kg of water-based dispersant, and 0.15kg of wetting agent.
[0072] A thermos cup coating is prepared according to the following steps:
[0073] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0074] Step 2: Add nano inorganic filler fumed silica while stirring, add 1kg of water to clean the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0075] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes. Add adhesion promoter and stir for 5 minutes. Then add wetting agent and stir for 5 minutes. Then add 1 kg of water and stir for 5 minutes to obtain the thermos cup coating.
[0076] Example 6
[0077] A thermos cup coating, the formula of which is as follows:
[0078] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano inorganic filler, 0.5kg of adhesion promoter prepared in Preparation Example 1, 1.5kg of water, 0.1kg of pH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, and 0.075kg of wetting agent.
[0079] A thermos cup coating is prepared according to the following steps:
[0080] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0081] Step 2: Add the nano inorganic filler hydroxylated carbon nanotubes while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0082] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes, add adhesion promoter and stir for 5 minutes; then add wetting agent and stir for 5 minutes, add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0083] Example 7
[0084] A thermos cup coating, the formula of which is as follows:
[0085] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano-inorganic filler (0.1kg of fumed silica and 0.1kg of hydroxylated carbon nanotubes), 0.5kg of adhesion promoter prepared in Preparation Example 1, 1.5kg of water, 0.1kg of pH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, and 0.075kg of wetting agent.
[0086] A thermos cup coating is prepared according to the following steps:
[0087] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0088] Step 2: Add the nano inorganic filler hydroxylated carbon nanotubes while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0089] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes, add adhesion promoter and stir for 5 minutes; then add wetting agent and stir for 5 minutes, add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0090] Example 8
[0091] A thermos cup coating, the formula of which is as follows:
[0092] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano-inorganic filler, 0.5kg of adhesion promoter prepared in Preparation Example 1, 1.5kg of water, 0.1kg of pH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, 0.075kg of wetting agent, and 0.1kg of hydrofluoric acid.
[0093] A thermos cup coating is prepared according to the following steps:
[0094] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0095] Step 2: Add nano inorganic filler fumed silica while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0096] Step 3: Add water-based amino resin, water-based acrylic resin and hydrofluoric acid to the ground slurry and stir for 5 minutes, add adhesion promoter and stir for 5 minutes; then add wetting agent and stir for 5 minutes, then add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0097] Example 9
[0098] A thermos cup coating, the formula of which is as follows:
[0099] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano-inorganic filler, 0.5kg of adhesion promoter prepared in Preparation Example 1, 1.5kg of water, 0.1kg of pH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, 0.075kg of wetting agent, and 0.3kg of hydrofluoric acid.
[0100] A thermos cup coating is prepared according to the following steps:
[0101] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0102] Step 2: Add nano inorganic filler fumed silica while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0103] Step 3: Add water-based amino resin, water-based acrylic resin and hydrofluoric acid to the ground slurry and stir for 5 minutes, add adhesion promoter and stir for 5 minutes; then add wetting agent and stir for 5 minutes, then add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0104] Example 10
[0105] A thermos cup coating, the formula of which is as follows:
[0106] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano inorganic filler, 0.5kg of adhesion promoter prepared in Preparation Example 1, 1.5kg of water, 0.1kg of pH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, 0.075kg of wetting agent, and 0.2kg of hydrofluoric acid.
[0107] A thermos cup coating is prepared according to the following steps:
[0108] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0109] Step 2: Add nano inorganic filler fumed silica while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0110] Step 3: Add water-based amino resin, water-based acrylic resin and hydrofluoric acid to the ground slurry and stir for 5 minutes, add adhesion promoter and stir for 5 minutes; then add wetting agent and stir for 5 minutes, then add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0111] Comparative Example
[0112] Comparative Example 1
[0113] A thermos cup coating, the formula of which is as follows:
[0114] 2kg polyester resin, 1.25kg water-based amino resin, 1.75kg water-based acrylic resin, 0.2kg nano inorganic filler, 1.5kg water, 0.1kg PH regulator, 0.2kg dipropylene glycol butyl ether, 0.025kg water-based dispersant, and 0.075kg wetting agent.
[0115] A thermos cup coating is prepared according to the following steps:
[0116] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0117] Step 2: Add nano inorganic filler fumed silica while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0118] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes; then add a wetting agent and stir for 5 minutes, then add 800g of water and stir for 5 minutes to obtain the thermos cup coating.
[0119] Comparative Example 2
[0120] A thermos cup coating, the formula of which is as follows:
[0121] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano inorganic filler, 0.5kg of polyurethane, 1.5kg of water, 0.1kg of PH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, and 0.075kg of wetting agent.
[0122] A thermos cup coating is prepared according to the following steps:
[0123] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0124] Step 2: Add nano inorganic filler fumed silica while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0125] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes, add adhesion promoter polyurethane and stir for 5 minutes; then add wetting agent and stir for 5 minutes, add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0126] Comparative Example 3
[0127] A thermos cup coating, the formula of which is as follows:
[0128] 2kg of polyester resin, 1kg of water-based amino resin, 1.5kg of water-based acrylic resin, 0.2kg of nano inorganic filler, 0.5kg of tannic acid, 1.5kg of water, 0.1kg of pH regulator, 0.2kg of dipropylene glycol butyl ether, 0.025kg of water-based dispersant, and 0.075kg of wetting agent.
[0129] A thermos cup coating is prepared according to the following steps:
[0130] Step 1: Weigh the polyester resin according to the amount and add it into the plastic jar. Install the jar on the disperser and fix it. Add the pH adjuster and stir for 5 minutes while the disperser is stirring. Then add dipropylene glycol butyl ether and stir for 5 minutes. Then add the aqueous dispersant and stir for 5 minutes.
[0131] Step 2: Add nano inorganic filler fumed silica while stirring, add 750g of water to wash the powder adhered to the tank wall, then disperse at 1000r / min for 15 minutes, and then use a sand mill to grind the slurry twice to a fineness of ≤5 microns.
[0132] Step 3: Add water-based amino resin and water-based acrylic resin to the ground slurry and stir for 5 minutes. Add adhesion promoter tannic acid and stir for 5 minutes. Then add wetting agent and stir for 5 minutes. Add 800g water and stir for 5 minutes to obtain the thermos cup coating.
[0133] Detection Methods
[0134] The coatings prepared in Examples 1-10 and Comparative Examples 1-3 were coated on stainless steel plates respectively, and then baked at 150° C. for 30 minutes to form coatings. The adhesion performance of the coatings was tested according to GB / T 5210-2006. The specific test results are shown in Table 2 below:
[0135] Table 2. Coating performance test
[0136]
[0137] It can be seen from Table 2 that the adhesion strength between the coating obtained by coating the coating prepared in the embodiment of the present application on a stainless steel plate (the material of the base layer of the thermos cup is mostly stainless steel) and the stainless steel plate is ≥18.4 MPa, and the adhesion strength is relatively high. The thermos cup coating prepared in the present application can solve the problem of poor adhesion between the coating and the thermos cup.
[0138] Combining Example 1 and Comparative Examples 1-3 and Table 2, it can be seen that the adhesion strength of the coating of Example 1 is much higher than that of Comparative Examples 1-3. This may be because: the adhesion promoter used in the raw materials of the coating of Example 1 is compounded by polyurethane and tannic acid in a certain mass ratio, and has the following effects: on the one hand, both the polyurethane and tannic acid molecules contain active groups, and there is interaction between these active groups and the active groups on the base layer of the thermos cup; on the other hand, tannic acid, as a chelating agent, can complex with the metal ions on the base layer of the thermos cup, and the interaction and complexation between the active groups jointly improve the adhesion performance between the coating and the base layer of the thermos cup; in summary, the adhesion promoter compounded by polyurethane and tannic acid in a certain mass ratio and other components in the raw materials of the thermos cup coating support each other functionally, and jointly improve the adhesion performance between the coating and the base layer of the thermos cup.
[0139] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A coating for a thermos cup, characterized in that: The invention comprises the following raw materials in parts by weight: 20-50 parts of polyester resin, 10-25 parts of water-based amino resin, 15-30 parts of water-based acrylic resin, 2-5 parts of nano inorganic filler, 5-15 parts of adhesion promoter and 15-25 parts of water; the adhesion promoter is prepared by compounding polyurethane and tannic acid in a mass ratio of (5-12):
1.
2. The coating for a thermos cup according to claim 1, characterized in that: The weight portion of the water-based amino resin is 20-25 parts.
3. The coating for a thermos cup according to claim 1, characterized in that: The weight portion of the water-based acrylic resin is 20-30 parts.
4. The coating for a thermos cup according to claim 1, characterized in that: The mass ratio of the polyurethane to tannic acid is (8-12):
1.
5. The coating for a thermos cup according to claim 1, characterized in that: The nano inorganic filler is one or more of fumed silica, hydroxylated carbon nanotubes, and graphene oxide.
6. The coating for a thermos cup according to claim 5, characterized in that: The nano inorganic filler is fumed silica and / or hydroxylated carbon nanotubes.
7. The coating for a thermos cup according to claim 5, characterized in that: The vacuum flask coating also contains 1-3 parts of hydrofluoric acid.
8. The coating for a thermos cup according to claim 7, characterized in that: The weight portion of the hydrofluoric acid is 1-2 parts.
9. A method for preparing a vacuum flask coating according to any one of claims 1 to 6, characterized in that: The steps include: The polyester resin, water-based amino resin, water-based acrylic resin, nano inorganic filler, adhesion promoter and water are mixed and stirred to obtain the thermos cup coating.
Citation Information
Patent Citations
Aqueous acrylic modified polyester industrial wheel hub coating material and preparation method thereof
CN109294416A
Waterborne amino stoving varnish for stainless steel vacuum cup and preparation method of waterborne amino stoving varnish
CN109401559A